Auditory Epistemology in Qur’anic Memorization: Reinterpreting Bi Al-Taghannī in Contemporary Tahfiz Education - Mohammad Zakariya Hariri Islam (TATHO: International Journal of Islamic Thought and Sciences, 2026)
Qur'anic tahfiz learning has expanded significantly in response to the growing interest in Qur'an-based education. Although previous studies have demonstrated the effectiveness of repetition-based approaches such as tikrar, muraja'ah, and sima'i, the cognitive role of bi al-taghanni has received limited theoretical attention and has generally been discussed as an aesthetic practice of Qur'anic recitation rather than as a memorization strategy. This article argues that bi al-taghanni functions as an auditory memorization strategy operating through cognitive mechanisms that facilitate encoding, storage, and retrieval during Qur'anic memorization. To substantiate this argument, the study reconceptualizes bi al-taghanni by integrating memorization theory and auditory learning into a unified conceptual framework. A qualitative library research design was employed through the systematic examination of relevant books, peer-reviewed journal articles, and scholarly publications using conceptual content analysis and interpretive synthesis. The findings suggest that the rhythmic and melodic characteristics of bi al-taghanni may strengthen memory formation by providing structured auditory stimulation that enhances attention, repetition, and long-term retention. This conceptual integration extends the scholarship of Qur'anic education by repositioning bi al-taghanni beyond its conventional role as a recitation technique toward an auditory memorization strategy with cognitive and pedagogical significance. The proposed framework offers a theoretical foundation for future empirical studies investigating the effectiveness of auditory-based memorization strategies in contemporary Qur'anic tahfiz education